Pengaruh dana pihak ketiga, biaya operasional pendapatan operasional (BOPO) dan kredit yang disalurkan terhadap kinerja keuangan pada sektor perbankan - Irma Br Hotang, Noni; Road Betterment Sitepu, Wilsa; Munte, Rupiwita; S, Serevina (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This study aims to analyze the effect of third party funds, operational costs of operating income and loan to deposit ratio on financial performance to test the sampling system used sampling saturation. This research produces a sample of 26 companies and then multiplied by 3 years of the testing period, the total sample size obtained as much as 78 data, analysis in research using annual financial reports, taken from the research method of multiple linear regression, classical assumption test and hypothesis testing using the F test and t-test through the SPSS program. The results show that third-party funds, operational costs of operational income, and loans have no effect on the financial performance of banking companies during the 2015-2017 period. This is shown by the model in this study of 6.5% which can explain the variation of the independent variables, the remaining 93.5% is explained by other variables outside the model. The discrepancies in the results of previous studies are caused by several things such as differences in the study period, research sector, and the number of research sample Â